2010
DOI: 10.1007/s12205-010-0307-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of shear wave velocity for characterizing clays from coastal regions

Abstract: Demand for infrastructure development in coastal regions where the subsurface is often composed of soft clays, results from the desire for rapid industrialization. The frequently encountered coastal soil conditions often call for suitable ground improvement and modification techniques to prepare soft deposits for foundation construction. For appropriate site improvement, several engineering soil properties are desired which require expensive and time consuming field and laboratory testing. Under such circumsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…All of equations 5, 6 and 7 were correlated only for sand-kaolin mixture with percentage of sand% between 30% to 80%. The comparison between the Gs, MDD, and CC results from current study and the outcomes from Kulkarni et al [19] indicated similarity between both results and conform the progressive relationships between Gs, MDD, and CC (see Figure 8).…”
supporting
confidence: 83%
“…All of equations 5, 6 and 7 were correlated only for sand-kaolin mixture with percentage of sand% between 30% to 80%. The comparison between the Gs, MDD, and CC results from current study and the outcomes from Kulkarni et al [19] indicated similarity between both results and conform the progressive relationships between Gs, MDD, and CC (see Figure 8).…”
supporting
confidence: 83%
“…MPa, respectively. By combining the current data with those given in previous studies (Kulkarni et al 2010;Long and Donohue 2010;Heitor et al 2013;Ogino et al 2015) where low to medium plasticity soils (PI ≤ 32) were tested under low confining pressure, the relationship between V s and void ratio e can be obtained (Fig. 4b).…”
Section: Effects Of Soil Density (Or Void Ratio)mentioning
confidence: 62%
“…It has been demonstrated by earlier researchers [100,121,122] that various geomechanical properties of the soil mass, viz., undrained shear strength, compression index, void ratio, elastic modulus and Poisson's ratio, can be determined in a noninvasive and nondestructive manner, easily, by correlating them to shear and compression wave velocities, V s and V p . Conventionally, resonant column, cyclic triaxial and torsional shear tests, which are quite intricate and expensive setups, have been employed for this purpose.…”
Section: Alteration In Geomechanical Propertiesmentioning
confidence: 99%